Noncholesteatomatous Cyst of the Tympanic Membrane: A Nonpublished Entity? - Rafael Ramírez-Camacho; Isabel Salas; Almudena Trinidad; Ithzel Maria Villarreal (Case Reports in Otolaryngology)
Introduction. The presence of a serous cyst in the tympanic membrane implies the description of a new or unpublished entity based on our knowledge whose origin may be very unlikely explained on actual embryologic and anatomic background. Clinical Case. We present a case of a 45-year-old woman with progressing right hearing loss. Physical examination revealed a whitish, round-shaped malformation in the posterior-inferior quadrant of the right tympanic membrane. The cyst was removed with a transcanal tympanoplasty. Discussion. A thorough PubMed search that involved the terms tympanic membrane gland, epithelial inclusion cysts, mucous-secreting cyst, and tympanic cyst has shown no positive results. The first description of an unknown entity, such as a tympanic membrane serous cyst, may be the key for clinicians to start paying attention to patients who suffer from similar pathologies and may pass unnoticed because of their rarity or peculiarity.